Simplify the expression: 2n + 10(9 + 4n)

Question

Simplify the expression:
2n + 10(9 + 4n)

in progress 0
Khải Quang 7 mins 2021-07-23T00:11:57+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-23T00:13:30+00:00

    Answer:

    42n+90

    Step-by-step explanation:

    0
    2021-07-23T00:13:32+00:00

    Answer: 42n+90
    Explaination:

    2
    n
    +
    10
    (
    9
    +
    4
    n
    )
    Distribute:
    =
    2
    n
    +
    (
    10
    )
    (
    9
    )
    +
    (
    10
    )
    (
    4
    n
    )
    =
    2
    n
    +
    90
    +
    40
    n
    Combine Like Terms:
    =
    2
    n
    +
    90
    +
    40
    n
    =
    (
    2
    n
    +
    40
    n
    )
    +
    (
    90
    )
    =
    42
    n
    +
    90

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )